EDITORIAL (Special Issue) - Teye, Prof. G. A. (UDS International Journal of Development, 2023)
The UDS International Journal of Development (UDSIJD) has published another Special Issue, Volume 10 No. 1, 2023. This Special Issue published papers from the Drylands Research Institute’s (DRI) annual conference on Water, Sanitation and Hygiene (WASH) in 2020. This Special Issue has a total of nineteen papers, seven in the Agricultural Sciences, nine in the Health Sciences, and three in the Humanities. All the manuscripts focus on different aspects of the Institute’s mandate. The Journal encourages all Directorates, Faculties and Schools of the University to publish their academic proceedings with us, as we are credible and offer open access to their research output, thus giving them a wider coverage. We continue to encourage researchers, academics, and authors from varied fields to submit their research manuscripts for consideration and publication. The Editorial Team will always be grateful to the University Management, authors, reviewers and staff of the Journal and all those who in diverse ways have supported in making this Special Issue of the Journal a reality. Prof. G. A. Teye (Editor-in-Chief)